Respuesta :
U=π(r+h)
r+h=U/π
r=U/π - h
Data:
U=16 1/2=16 + 1/2=(16*2+1)/2=33/2
h=2
π=22/7
Then:
r=U/π - h
r=(33/2)/(22/7) - 2
r=(33*7)/(2*22) - 2
r=231 /44 - 2
r=(231-2*44)/ 44
r=(231-88)/44
r=143/44 = (3*44 + 11)/44=3 11/44
Answer: r=143/44 or 3 11/44
r+h=U/π
r=U/π - h
Data:
U=16 1/2=16 + 1/2=(16*2+1)/2=33/2
h=2
π=22/7
Then:
r=U/π - h
r=(33/2)/(22/7) - 2
r=(33*7)/(2*22) - 2
r=231 /44 - 2
r=(231-2*44)/ 44
r=(231-88)/44
r=143/44 = (3*44 + 11)/44=3 11/44
Answer: r=143/44 or 3 11/44
U = π* (r + h ) [ : π
[tex] \frac{U}{ \pi } = r + h \\ \\ r = \frac{U}{ \pi } - h \\ \\ r = \frac{16,5}{ \pi } - 2 \\ \\ r = \frac{165}{10} : \frac{22}{7} - 2 \\ \\ r = \frac{33}{2} * \frac{7}{22} - 2 \\ \\ r = \frac{3}{2} * \frac{7}{2} - 2 \\ \\ r = \frac{21}{4} - 2 = 5,25 - 2 = 3.25 Answer r = 3,25[/tex]
[tex] \frac{U}{ \pi } = r + h \\ \\ r = \frac{U}{ \pi } - h \\ \\ r = \frac{16,5}{ \pi } - 2 \\ \\ r = \frac{165}{10} : \frac{22}{7} - 2 \\ \\ r = \frac{33}{2} * \frac{7}{22} - 2 \\ \\ r = \frac{3}{2} * \frac{7}{2} - 2 \\ \\ r = \frac{21}{4} - 2 = 5,25 - 2 = 3.25 Answer r = 3,25[/tex]